2017
DOI: 10.1177/0954410017699008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nozzle configuration on the flow field of multiple jets

Abstract: Turbulent jet flows with multiple nozzle inlets are investigated computationally using OpenFOAM. The configurations vary from single to five axisymmetric nozzles. First-order closure is used with Reynolds-averaged Navier-Stokes equations. Computed results are compared with the available experimental data. The effect of nozzle configuration on the jet flow field is discussed with predicted mean flow and turbulent flow data. Near-field of multiple jets shows the nonlinear behavior. Multiple jets show better perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The analysis shows that, when the distance between the discharge ports is larger, the interaction between sub-jets is smaller, but the mixing degree between the rear sub-jets and environmental water is greater in the flow direction of the environmental water. Kannan et al [20] calculated the thermal jet flow field from one discharge port to five discharge ports by using the open-source computing platform and compared it with relevant experimental data. The calculations show that the near field flow characteristics of porous jet are nonlinear.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis shows that, when the distance between the discharge ports is larger, the interaction between sub-jets is smaller, but the mixing degree between the rear sub-jets and environmental water is greater in the flow direction of the environmental water. Kannan et al [20] calculated the thermal jet flow field from one discharge port to five discharge ports by using the open-source computing platform and compared it with relevant experimental data. The calculations show that the near field flow characteristics of porous jet are nonlinear.…”
Section: Introductionmentioning
confidence: 99%
“…Through the flow characteristics analysis, they demonstrated that the mixing between the swirling jets generated a temperature distribution along the centerline and near the blowing diffusers, while allowing the resulting jet to propagate. Kannan and Panchapakesan (2017) numerically studied multiple circular jets (from one to five) flowing into a calm air environment using Open FOAM computation code. They compared their findings to the available experimental data and found that it is the standard k-ε turbulence model that satisfactorily reproduces the non-linear decay of the mean axial velocity for the multiple jets case.…”
Section: Introductionmentioning
confidence: 99%
“…This non-linear behavior can be utilized in applications that need better mixing. It was also shown that usage of higher number of nozzles results in higher mixing (Kannan and Panchapakesan, 2017).…”
Section: Introductionmentioning
confidence: 99%